2015
DOI: 10.1016/j.gloenvcha.2015.01.013
|View full text |Cite
|
Sign up to set email alerts
|

An intergenerational transmission of sustainability? Ancestral habitus and food production in a traditional agro-ecosystem of the Upper Guinea Forest, West Africa

Abstract: The need for sustainable alternatives to industrial farming has led to a revival of interest in traditional agro-ecosystems. Whilst it is well recognised that traditional agro-ecosystems are both social and physical-technical-few case studies have examined interactions between both these dimensions in a single system. For a system to be considered sustainable it needs to be shown to have retained key characteristics over several generations. Case studies therefore demand a location where intergenerational tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Such strategies also play an important role for reducing the impact of food and nutrition insecurities [31,32]. Transhumance pastoral systems offer considerable value for sustainability through their ecological knowledge, indigenous practices, beliefs, and culture, which enhances the capacity and resilience of traditional agro-pastoral systems [33][34][35]. The integration of such knowledge, when combined with scientific approaches and technologies, may also result in the effective management of livestock and rangeland resources [36,37].…”
Section: Changing Livelihood Of the Pastoral Communitiesmentioning
confidence: 99%
“…Such strategies also play an important role for reducing the impact of food and nutrition insecurities [31,32]. Transhumance pastoral systems offer considerable value for sustainability through their ecological knowledge, indigenous practices, beliefs, and culture, which enhances the capacity and resilience of traditional agro-pastoral systems [33][34][35]. The integration of such knowledge, when combined with scientific approaches and technologies, may also result in the effective management of livestock and rangeland resources [36,37].…”
Section: Changing Livelihood Of the Pastoral Communitiesmentioning
confidence: 99%
“…Also of interest have been tropical rainforest anthrosols such as the fertile terra preta soils of the pre-Columbian Amazon. Research into these pre-Columbian soilscape legacies has both encouraged the search for pantropical analogues [107][108] and inspired attempts to recreate similarly fertile soils 109 .…”
Section: The Deep History Of Global Tropical Forests: Implications Fomentioning
confidence: 99%
“…This system, however, is under threat from a generational shift in cultural valuation. Youth across NW Liberia participated in the recent (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005) war, which accelerated already existing processes of change wherein youth begin to challenge various aspects of the Loma worldview, including the sacredness of SA, i.e., that they should not be cleared for annual crop production (Fraser et al 2015). This is demonstrated in our survey that found that when SA were slashed, it was often by youth in violation of their elders' wishes.…”
Section: Cultural Processes Shaping Sacred Agroforestsmentioning
confidence: 99%
“…SA are located at the sites of ruined towns belonging to Mande macro-language speaking groups who have occupied the region for more than 500 years (Brooks 1989). Owing to considerable cultural continuity in the region, despite historic and recent wars, current populations are normally descendants of the historical occupants of these towns, and are conferred tenurial rights by ritualized relationships with their ancestors (Fraser et al 2015). We focus on one group in particular, the Loma.…”
Section: Introductionmentioning
confidence: 99%